Up-regulation of DLL1 May Promote the Chemotherapeutic Sensitivity in Small Cell Lung Cancer - Huanxin LIU; Juan PENG; Yifeng BAI; Linlang GUO (Chinese Journal of Lung Cancer, 2013)
Background and objective Delta-Like1 (DLL1) can combine with Notch receptor and activate the Notch signal pathway, then made a decision to cell differentiation and regulate the development of many tissues. It is proved that DLL1 was highly correlated with tumor’growth and differentiation, our previously study showed that DLL1 was associated with MDR in small cell lung cancer (SCLC). The aim of this study is to furtherly investigate the role of DLL1 gene in small cell lung multi-drug resistance. Methods Firstly, the analysis of qRT-PCR and Western blot were used to study differential expression of DLL1 from mRNA and protein levels in both the H69 and H69AR cell lines. Then, we developed a stably DDL1 overexpressing H69AR-eGFP-DLL1 subline, by transfection with DLL1-pIRES2-EGFP. Moreover, the sensitivities of cells to chemotherapy drugs such as ADM, DDP, VP-16 were detected by CCK8 assay. The change of cell cycle and apoptosis rate were detected by flow cytometry. Results The expression of DLL1 was significantly decreased in H69AR cells than that in the H69 cells. The sensitivities of H69AR cells to chemotherapy drugs were increased when up-regulated the expression of DLL1, enforced DLL1 expression increased cell apoptosis and the cell cycle arrest in G0/G1 and S phase in H69AR cells, the expression of downstream genes HES1 and HEY1 were increased after transfected with DLL1-pIRES2-EGFP. Conclusion Our results suggest that overexpression of DLL1 in small cell lung cancer may increase the sensitivity of cells to chemotherapeutic agents. DLL1 influence drug resistance of small cell lung cancer through activating transcription of downstream genes HES1 and HEY1.